Manajemen Kedisiplinan Siswa di SMP Negeri 14 Surakarta - Rahayu, Endang Puji (Journal of Profession Education, 2021)
This study aims to describe: 1) student discipline planning at SMP Negeri 14 Surakarta, 2) student discipline implementation at SMP Negeri 14 Surakarta, and 3) student discipline control at SMP Negeri 14 Surakarta. This type of research is a qualitative research with a case study design. Data collection techniques using the method of observation, interviews, and documentation. Data validity uses triangulation of sources and techniques. Data analysis techniques using interactive model analysis. The results of the study shows: 1) Student discipline planning is done through the identification of problems showing students are often late for school. The determination of ideas and ideas was demonstrated by the principal's meeting with all the teachers who set the innovation program "Palaska Breakfast Menu" who are voluntary and do not exploit students. Coordination and policy making by issuing Team Decrees, making designs, preparing infrastructure, and socializing. 2) Implementation of student discipline is done by arranging a life together through program socialization, The teacher gives an example of obeying school rules and maintaining good relations with students. Planting a sense of sincerity for students, awareness of students to be more disciplined, the teacher pays attention to students who are experiencing problems and helps overcome them, communication with students' parents, provides strict punishment for disciplinary offenders based on time delays and contains elements of learning. Creating a conducive environment by inviting all teachers to be role models for students. 3) Control of student discipline is done through classroom discipline, inviting students to maintain cleanliness and make a daily picket schedule, take preventive measures by reminding each other, socializing by installing school rules, invite all components of the school to obey the school rules as daily habits, establishing relationships with students and collaboration with students' families.